Multimodal Retrieval in the Medical Domain First International Workshop, MRMD 2015, Vienna, Austria, March 29, 2015, Revised Selected Papers - Müller, Henning; Jimenez del Toro, Oscar Alfonso; Hanbury, Allan; Langs, Georg; Foncubierta Rodriguez, Antonio (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
This book constitutes the proceedings of the First International Workshop on Multimodal Retrieval  in the Medical Domain, MRMD 2015, held in Vienna, Austria, on March 29, 2015. The workshop was held in connection with ECIR 2015. The 14 full papers presented, including one invited paper, a workshop overview and five papers on the VISCERAL Retrieval  Benchmark, were carefully reviewed and selected from 18 submissions. The papers focus on the following topics: importance of data other than text for information retrieval; semantic data analysis; scalability approaches towards big data sets.